Attitudes, Sentiments, and Concerns About Inclusive Education of Teachers and Teaching Students in Spain - Navarro-Mateu, Diego; Franco-Ochoa, Jacqueline; Valero-Moreno, Selene; Prado-Gascó, Vicente (Frontiers in Psychology, 2020)
Sentiments, Attitudes, and Concerns about Inclusive Education Revised was developed to close the 16 existing gap in measuring perceptions of inclusive education in the educative context. It has been 17 widely used in other cultures, but not in Spain. Our objective has been to analyse the psychometric 18 properties in the Spanish sample by studying their relationship with empathy and social dominance 19 variables, and finally taking into account sociodemographic variables to observe if there are 20 differences. The scale was applied to a total of 647 subjects: 323 university-students (18-45 years) and 21 324 in-service teachers (35-58 years). The scale showed psychometric properties suitable for general 22 group and the students, and teachers. Likewise, the female students showed a more positive attitude 23 towards inclusion and these attitudes were associated with empathy and social dominance. This version 24 of the Sentiments, Attitudes, and Concerns about Inclusive Education Revised is a useful tool for 25 measuring the inclusive attitudes of undergraduate Education students and in-service teachers.